PTU-193 A Novel, Rational Approach to Treating Primary Bile Acid Diarrhoea: a Proof of Concept Study of the FXR Agonist Obeticholic Acid. (4th June 2013) - Johnston, I; Nolan, J D; Dew, T; Shapiro, D; Walters, J R
Abstract : Introduction: Primary (idiopathic) bile acid diarrhoea (PBAD) is a common chronic diarrhoeal condition, affecting 1% of the population, and a large proportion of patients otherwise diagnosed with IBS-D. We showed that the ileal hormone Fibroblast Growth Factor 19 (FGF19), which decreases hepatic bile acid (BA) synthesis, is reduced in this condition, resulting in excess BA production and faecal BA loss. FGF19 is secreted in response to the natural farnesoid X receptor (FXR) agonist chenodeoxycholic acid (CDCA). Obeticholic acid (OCA), 6-ethyl CDCA, is a semi-synthetic derivative with 100x greater FXR agonist potency. We aim to determine the FGF19, BA and clinical response to OCA in PBAD patients. Methods: After a 2-week run in period, 10 patients (7F:3M, median age 47, range 24–74) with PBAD (SeHCAT 7d retention < 10%, median 4.8%), received oral OCA 25mg daily, for 2 weeks. Bile acid sequestrants were discontinued; loperamide was allowed as rescue therapy. Patients completed symptom diaries including stool frequency and Bristol Stool-form Scale (BSFS); a diarrhoea index ([stool frequency * mean BSFS] + loperamide use [weekly mg*3]) was calculated. Fasting serum FGF19 and total BA were measured before the first dose of OCA and after 2w treatment. Postprandial FGF19 and BA (6h area-under-curve, AUC) were determined after the first and last OCA dose. Data (expressed as medians) were analysed by Wilcoxon paired tests and Spearman correlation. Results: OCA increased fasting FGF19 from 133 to 237 pg/ml (p = 0.007) at 2w. Most patients had an increase > 60% in fasting FGF19 and a large OCA first dose/postprandial response. Fasting BA reduced from 1.5 to 0.9 µmol/l (p = 0.13) and postprandial BA AUC was lower after the 2 w OCA treatment (from 4.9 to 3.0 µmol/l, p = 0.02). Clinical improvements were found in all patients, including in stool frequency (23 to 14/wk, p = 0.02), BSFS (5.15 to 4.34, p = 0.05) and the diarrhoea index (113 to 76, p = 0.005). The reduction in BA AUC (p = 0.02) and the increase in fasting FGF19 (p = 0.03) both correlated with the reduction in stool frequency. Symptoms of abdominal pain, urgency and bloating also tended to be less on OCA treatment. OCA was well tolerated and no adverse events were reported of clinical concern. Conclusion: This study has shown for the first time that rational therapy with the FXR agonist OCA in PBAD is well tolerated and effective, stimulating serum FGF19 and reducing postprandial BA, resulting in clinical improvements in stool frequency and type. We propose larger, randomised, controlled trials of OCA. [EudraCT 2011–003777–28] Disclosure of Interest: None Declared.